Implementation of Population Administration Service Policies During the Covid-19 Pandemic in Garut Regency - Ikeu Kania (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
The Covid-19 pandemic that has run rampant globally has made administration complicated and time-consuming. The Minister of Home Affairs issued Permendagri No. 7 of 2019 concerning Online Population Administration Services, which the Garut Disdukcapil then implemented by creating a Pandu-Online service. This online service has only been implemented at the Garut Disdukcapil because previously, the service was carried out directly. This study aims to determine the implementation of population administration service policies during the COVID-19 pandemic in Garut Regency and determine the supporting and inhibiting factors for implementing population administration service policies during the COVID-19 pandemic in Garut Regency. Researchers used a descriptive method with a qualitative approach. Data sources were taken from the Garut Disdukcapil and community users of these services, with data collection methods carried out in observations and interviews. The results of this study explain that the implementation process does not always run as it should; in the field, there are still many obstacles that exist, so the implementation process has not run well and optimally. Garut Disdukcapil parties need to make many improvements so that the entire community of Garut Regency can feel the implementation of this policy.